2008
DOI: 10.1111/j.1365-2362.2008.01941.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of inducible nitric oxide synthase activity prevents liver recovery in rat thioacetamide‐induced fibrosis reversal

Abstract: Both NOS inhibitors developed a clear pro-fibrotic effect in the liver. Aminoguanidine was more fibrotic than L-NAME. Our data suggest a significant anti-fibrotic role for iNOS rather than for eNOS. L-Arginine did not show any anti-fibrotic properties in the TAA-model used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 42 publications
(42 reference statements)
1
19
0
Order By: Relevance
“…CD68-positive cells were also evidently reduced in this group (figs 2, 3 and 4). These findings concur with that of Lukivskaya et al [70] who have found that TAA withdrawal led to partial spontaneous reversibility of liver fibrosis together with a decreased fibrosis rate. However, the incomplete recovery of the aforementioned parameters in this group proposed the persistence of both inflammatory and fibrotic reactions even after TAA withdrawal.…”
Section: Discussionsupporting
confidence: 93%
“…CD68-positive cells were also evidently reduced in this group (figs 2, 3 and 4). These findings concur with that of Lukivskaya et al [70] who have found that TAA withdrawal led to partial spontaneous reversibility of liver fibrosis together with a decreased fibrosis rate. However, the incomplete recovery of the aforementioned parameters in this group proposed the persistence of both inflammatory and fibrotic reactions even after TAA withdrawal.…”
Section: Discussionsupporting
confidence: 93%
“…1f), indicating that inhibition of NO production in the early phase of muscle healing could shift the balance toward scar formation instead of muscle repair. A number of studies have indicated that NO stimulates collagen synthesis in various cell types, such as afferent arterioles, vascular smooth muscle cells, pulmonary tissue, cutaneous wounds and Peyronie's disease tissue from both human specimens and a rat model of PD [50][51][52][53][54][55], but the role of NO in the regulation of collagen levels in a crush muscle injury model has not been studied previously.…”
Section: Discussionmentioning
confidence: 99%
“…During liver fibrosis, however, eNOSderived NO is reduced [8]. In in vivo studies, NO plays an inhibitory role in the development of liver fibrosis while iNOS deficiency and reduced eNOS expression with liver injury result in exacerbation of liver fibrosis [9,10]. Accordingly, the NO donor S-nitroso-N-acetylcysteine attenuates fibrosis [11].…”
Section: Introductionmentioning
confidence: 99%